Kajian Kesesuaian dan Keberkesanan Raven SPM untuk Mengenal Pasti Kanak-kanak Melayu yang Pintar Cerdas - Mohd Isa, Abd Majid (Universiti Putra Malaysia Press, 1994)
The objective of this study is to determine the suitability of Raven's SPM as a group intelligence test for the screening of gifted children. One hundred Form One Malay students from Sekolah Menengah Datuk Abdullah, Rembau were the respondents in the study. They were among the high achievers in the 1990 Ujian Pencapaian Sekolah Rendah at Tampin/Rembau District who qualified to be emplaced at residential schools. The Raven's SPM and WISC-R were administered. Students with IQ scores of more than 120 on the WISC-R are classified as gifted. The correlation between the Raven's SPM score and the IQ score derived from the WISC-R was high and seemed to share about 65 percent of the 'intelligence' costruct. From the regression equation, the giftedness construct could be drawn from a Raven's SPM score of50. However, the standard error for this equation was also notably high. Therefore, many of the gifted children may be among those with a Raven's score ofless than 50 and this is known as false negative. The effectiveness and efficiency indexes forwarded by Pegnato and Birch (1959) were used in determining whether a score lowe, than 50 on the Raven's SPM would reduce the false negative. As the lower score would increase the number of children to be tested, the score recommended must be cost effective. A score of 48 was recommeded as it reduces the number to be tested to 30 percent, and includes 85 percent of the gifted children. Also, the efficiency is high compared with other scores. Using this procedure, it is estimated that one among three children studied is gifted.